The altered apoptotic pathways in cisplatin and etoposide-resistant melanoma cells are drug specific - Kissel, Christine Katharina; Schadendorf, Dirk; Röckmann, Heike (Melanoma research, 2006)
Apoptotic deficiency is one of the mechanisms leading to chemoresistance due to the potential of many chemotherapeutic drugs to induce apoptosis. We have examined drug-induced apoptosis in the chemosensitive human melanoma cell line MeWo, as well as in its resistant sublines, which were selected by continuous exposure to etoposide (MeWoEto1) and cisplatin (MeWoCis1). In former studies, activation of the mitochondrial pro-apoptotic pathway could not be demonstrated in etoposide-resistant cells after exposure to etoposide. A significant reduction of PARP [poly (ADP-ribose) polymerase] cleavage and caspase activation, but unimpaired DNA fragmentation, was seen in cisplatin-resistant cells after treatment with cisplatin. In the current study, we investigated effects of chemotherapeutic drugs different from the selecting agents cisplatin and etoposide on the observed modulations of the mitochondrial apoptotic pathway. We analysed dose-dependent release of cytochrome c, caspase-9 activation, cleavage of PARP and activation of effector caspases in etoposide and cisplatin-resistant cells after exposure to etoposide, teniposide, cisplatin or fotemustine. In analogy to etoposide exposure, we could not demonstrate any activation of the apoptotic pathway in etoposide-resistant cells after exposure to teniposide, another topoisomerase-II inhibitor. In contrast, exposure to cisplatin and fotemustine led to apoptotic cell death in these cells. This suggests that the deficiency of apoptosis in etoposide-resistant cells is dependent on the trigger by topoisomerase-II inhibitors. Analysis of cisplatin-resistant cells after etoposide and fotemustine exposure revealed an increased activity of the apoptotic pathway when compared with cisplatin exposure at corresponding survival rates in these cells. These results suggest that the observed modulations of the apoptotic pathway in resistant melanoma cell lines are specific for an anti-neoplastic drug and are not fixed at the molecular level, as different chemotherapeutic drugs are capable of overcoming these alterations.